THE ONE MEMORY OF FLORA BANKS - Barr, Emily; Dolan, Hannah; Castano, Julia; Pitts, Sorrel (London : Penguin Books, 2021)
"Seventeen-year-old Flora Banks has an illness and can't remember anything for very long. She writes notes to herself to help her remember things. But on day, Flora kisses a boy and she remembers it. Flora must find the boy who kissed her and learn why she still has that one memory." -- back cover
Includes questions and excercises
Keywords: Teenage girls -- Fiction; Amnesia -- Fiction